2015
DOI: 10.1097/jto.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

High Discrepancy of Driver Mutations in Patients with NSCLC and Synchronous Multiple Lung Ground-Glass Nodules

Abstract: We found a high discrepancy of driver mutations among NSCLC patients with GGNs and a favorable prognosis after multiple lesions resection, which support surgical resection in this situation as a reasonable approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
107
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 39 publications
10
107
3
Order By: Relevance
“…While, different observations were found last year (19,20). One of the studies enrolled 35 patients with 72 lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, different observations were found last year (19,20). One of the studies enrolled 35 patients with 72 lesions.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies enrolled 35 patients with 72 lesions. Among them, 33 (45.8%) tumor lesions were found harboring EGFR mutations, and their founding indicated that there was a high discrepancy of driver mutations in NSCLC patients with ground-glass nodules (GGNs) (19). Another research showed that EGFR mutation especially L858R was detected more frequently in invasive solid pattern and significantly less in pure GGO pattern in stage I lung adenocarcinoma (21).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the previously published studies regardless of methodological approaches. 2,6,7,10,[23][24][25] The presence of discordant mutations most likely can be used as an indicator of a different clone. Earlier studies indicated a broad range of discordance (25-49%) in driver mutations (EGFR, KRAS) between primary and metastatic lung tumors that in part can be explained by different methodological approaches, although authors mostly suggested intratumoral heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…It is striking that many studies, including ours, failed to demonstrate correlation between clonality defined by genotype and outcomes. 9,10 Therefore, it is uncertain whether different mutations identify separate primary cancers or just a different clone within single tumor. Large prospective studies with precisely defined treatment management could potentially provide the answer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation